HPLC Determination of Enantiomeric Purity for 1-Styrene-3-Hexyl Propynol. (30th November 2016) - Chen, Ping; Wei, Siping; Wang, Li; Tang, Bin; Wang, Shu; Wang, Qin; Du, Xi
Abstract: A rapid and sensitive high performance liquid chromatography method was developed and validated for the determination of enantiomeric purity of 1-styrene-3-hexyl propynol. Baseline separation with resolution greater than 2.0 was achieved within 17 min on a CHIRALCEL OD-H (25 cm × 0.46 cm; particle size 5 μm) column using n -hexane:isopropanol (95:5 v / v ) as mobile phase at a flow rate of 1 mL·min −1 and 25°C as column temperature. The analytes were detected by UV absorbance at 210 nm. The effects of column, composition of mobile phase, temperature and flow rate on the chromatography were investigated. The method was extensively validated and proved to be robust. The recoveries were in the range of 99.6–102.6% with relative standard <0.32%. The limit of detection and limit of quantitation for (S)-1-styrene-3-hexyl propynol were 0.0041 and 0.22 μg·mL −1, and for (R)-1-styrene-3-hexyl propynol were 0.0036 and 0.19 μg·mL −1, respectively. This method was proved to be accurate, stable, rapid and sensitive for the determination of enantiomeric purity of 1-styrene-3-hexyl propynol and its homologs.